Analysing the accuracy of asymptotic approximations in incomplete contact problems. (15th October 2022) - Moore, M.R.; Hills, D.A.
Abstract: The error incurred in the representation of the contact pressure at the edges of incomplete contacts by first order asymptotes is treated, and the maximum value of the relative error found for a range of geometries, both symmetric and non-symmetric. For a symmetric power-law geometry, we identify when the first-order asymptote achieves maximum fidelity. Shear tractions are excited by both the application of a shear force and the application of bulk tension in one body. An asymptotic representation of the shear traction distribution under conditions of full stick is presented.